Evaluación de la relación de fracturas en estado crítico de esfuerzo con las pérdidas de circulación en un pozo de Ecopetrol S.A. (2017)
In the current work it was evaluated the Mohr-Coulomb criteria in the natural fractures that were present in a well, with the purpose of evaluate if those fractures were critically stressed or not, and looking for the relation with mud loss, based on the theory that critically stressed fractures are hydraulically conductive, in the work could be possible to determinate the relation between the stress state, the orientation of natural fractures and mud loss, showing critically stressed fractures in the mud loss zones.